ANALISIS SEBARAN PENCEMARAN LINDI (LEACHATE) BERDASARKAN SIFAT KELISTRIKAN BATUAN MENGGUNAKAN METODE GEOLISTRIK - Ninik Agustin; Siti Fauzatun Wachidah (KURVATEK, 2021)
Jeruklegi landfill has leachate management system that still potential for leachate infiltration in subsurface. Leachate contamination may occur if landfill activity is continuous and have an impact to local society. Leachate contamination is an environmental pollution man-made minor disaster clasified. This research is an early prevention step by identifying disaster source. Identification is done by analyzing leachate distribution in subsurface using geoelectrical method with Wenner-Schlumberger array. The result of data acquisition is resistivity which is processed to apparent resistivity. Apparent resistivity was modelled by inversion method that shows leachate contamination near surface by resistivity not least at 1 ohm.m. Leachate contamination was not found over 20 meters based on the lack of resistivity difference. This was confirmed by chemical test of bore well water that match to hygiene and sanitation standards. Keywords: leachate, resistivity, geoelectric, Wenner-Schlumberger.